2017
DOI: 10.1371/journal.pone.0188097
|View full text |Cite
|
Sign up to set email alerts
|

All-cause mortality among diabetic foot patients and related risk factors in Saudi Arabia

Abstract: BackgroundAlthough Diabetes mellitus is a major public health problem in the Middle East and North Africa (MENA) region with high rates of diabetic foot complications, there are only limited data concerning mortality among such a high risk group. Therefore, the main aim of the current study was to assess all-cause mortality and its related predictors among diabetic patients with and without diabetic foot complications.MethodsUsing data from the Saudi National Diabetes Registry (SNDR), a total of 840 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 30 publications
6
49
2
6
Order By: Relevance
“…This is due to the disease condition to increase its severity from time to time if not adequately controlled. This finding is in line with other studies that were, as the duration of patients live with diabetic Mellitus increase, the occurrence of diabetic foot ulcer also increased [35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Discussionsupporting
confidence: 93%
“…This is due to the disease condition to increase its severity from time to time if not adequately controlled. This finding is in line with other studies that were, as the duration of patients live with diabetic Mellitus increase, the occurrence of diabetic foot ulcer also increased [35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Discussionsupporting
confidence: 93%
“…A recent study from Saudi Arabia reported similar ndings of nephropathy being an independent risk factor for all-cause mortality among patients with diabetic foot complications. 45 Given the high mortality of hospitalized DFU patients in our setting, identi cation of the above-stated prognosticators is crucial to guide strategies for improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Although there is the paucity of data regarding the factors associated with intra-hospital mortality in Nigerian patients with DFU, reports from other parts of the world indicate that lower extremity amputation (LEA) conferred a higher risk of mortality. 6 Malnutrition, con rmed using a geriatric nutritional assessment risk index was found to be associated with higher mortality among patients admitted for DFU in concert with older age and reduced glomerular ltration rate. 10,11 The Site of osteomyelitis (hind versus mid/forefoot) was a determinant of higher mortality in a cohort of DFU patients in Arezzo, Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia is linked to dysfunction and long-term damage to numerous body organs such as kidneys, blood vessels, eyes, heart, and nerves. Diabetes is currently on the rise worldwide and is connected to the high morbidity and mortality rates [5]. Diabetes mellitus occurs in two main types: type 1, and type 2 although there is a third diabetes type known as gestation diabetes though not universal [5].…”
Section: Theme 1: Self-efficacy Behaviour Prevention and Management Ofmentioning
confidence: 99%